Intervening for Good: Governmental Intervention for Enhancing Service Worker Capability in Hospitality Business - Mahmud, Amir (Jurnal Minds: Manajemen Ide dan Inspirasi, 2023)
In the vibrant world of hospitality, the workforce serves as the pillar of regional tourism growth. The symbiotic relationship between hotel staff, the service providers, and guests, the consumers, is at the heart of this industry. Hotels, therefore, must continually enhance their staff quality, as they are the hotel’s living embodiment. Recognizing this, the Indonesian government has implemented certification programs through the Tourism Office to maintain service standards. This study delves into the impact of such interventions on service quality. It juxtaposes the self-evaluation of workers (n=325) post-intervention with customer perceptions (n=454), revealing a positive correlation between government intervention, employee self-assessment, and customer satisfaction.